2018
DOI: 10.1186/s13722-018-0112-6
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the effect of methamphetamine on traumatic injury complications and outcomes

Abstract: BackgroundThis study investigates the impact of methamphetamine use on trauma patient outcomes.MethodsThis retrospective study analyzed patients between 18 and 55 years old presenting to a single trauma center in San Bernardino County, CA who sustained traumatic injury during the 10-year study period (January 1st, 2005 to December 31st, 2015). Routine serum ethanol levels and urine drug screens (UDS) were completed on all trauma patients. Exclusion criteria included patients with an elevated serum ethanol leve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 26 publications
1
16
0
1
Order By: Relevance
“…In general, the effect of pre-injury illicit drug use on outcomes is controversial and the reported results are often contradictory [ 11 , 13 16 , 19 , 20 ]. Important factors that can confuse the interpretation of results are inclusion of all illicit drugs in one group, as well as the presence of multiple injuries.…”
Section: Discussionmentioning
confidence: 99%
“…In general, the effect of pre-injury illicit drug use on outcomes is controversial and the reported results are often contradictory [ 11 , 13 16 , 19 , 20 ]. Important factors that can confuse the interpretation of results are inclusion of all illicit drugs in one group, as well as the presence of multiple injuries.…”
Section: Discussionmentioning
confidence: 99%
“…In a study of patients in the intensive care unit, Kram et al did not detect a difference in sedation requirements between patients who were acutely intoxicated on stimulants and non-intoxicated patients 72 . However, case studies have indicated that both acute and chronic methamphetamine abuse can alter anesthesia requirements 18,72,73 . Cases of cardiac arrest, refractory hypotension, and severe intraoperative intracranial hypertension due to methamphetamine’s impact on anesthesia requirements have implicated the neurologic effects of methamphetamine 18,73 .…”
Section: Perioperative Care Of Patients With Acute Methamphetamine In...mentioning
confidence: 99%
“…However, case studies have indicated that both acute and chronic methamphetamine abuse can alter anesthesia requirements 18,72,73 . Cases of cardiac arrest, refractory hypotension, and severe intraoperative intracranial hypertension due to methamphetamine’s impact on anesthesia requirements have implicated the neurologic effects of methamphetamine 18,73 . These studies have contributed to the idea that patients with elevated cortical awareness from acute abuse of methamphetamine may require higher anesthetic doses, but also that catecholamine depletion that is associated with chronic abuse may result in a lower requirement for anesthesia.…”
Section: Perioperative Care Of Patients With Acute Methamphetamine In...mentioning
confidence: 99%
“…Methamphetamine (MA), colloquially known as crystal meth, speed, or ice, is a highly addictive illegal drug that is a potent central nervous system psychostimulant that causes deficits in memory, executive functions, information processing, and motor skills (1). It also induces euphoria, aggression, and erratic behavior and has been found on toxicological testing at all ages (2)(3)(4)(5)(6). MA is associated with high dependency rates and its potential for abuse has been linked to overdoses, drug-related crime, and traumatic deaths including vehicle occupant fatalities (7)(8)(9)(10).…”
Section: Introductionmentioning
confidence: 99%